Practicing subversive social work from the standpoint of the ecological theory and social learning theory: A tool for academic learning - Blessing Ramsey-Soroghaye; Sotonye Gobo (Institute of Computer Science (IOCS), 2022)
Application of theories in social work practice is not new. The profession of social work is a helping one. Subversion on the other hand attempts to transform the established social order and its structures of power, authority and hierarchy. It is the process by which the values and principles of a system in place are contradicted or reversed. So, what is obtainable as social work in the Western world is adjusted in an attempt to indigenize social work in Nigeria. This article reports on an exploratory study of ecological theory and social learning theory in practicing subversive social work. The study found that ecological theory enables the social worker understand the culture while social learning theory helps in understanding the behavioural and adjustment patterns of clients through modeling and imitation. This study recommends that the curriculum of social work has room for subversion and indigenization and also, lenses should be put on core social work theories that promote the core values, principles, methods and roles of social workers.